Missed opportunities for HIV testing among those who accessed sexually transmitted infection (STI) services, tested for STIs and diagnosed with STIs: a systematic review and meta‐analysis. Issue 4 (26th April 2023) - Saleem, Kanwal; Ting, Ee Lynn; Loh, Andre J. W.; Baggaley, Rachel; Mello, Maeve B.; Jamil, Muhammad S.; Barr‐Dichiara, Magdalena; Johnson, Cheryl; Gottlieb, Sami L.; Fairley, Christopher K.; Chow, Eric P. F.; Ong, Jason J.
Abstract: Introduction: Of 37.7 million people living with HIV in 2020, 6.1 million still do not know their HIV status. We synthesize evidence on concurrent HIV testing among people who tested for other sexually transmitted infections (STIs). Methods: We conducted a systematic review using five databases, HIV conferences and clinical trial registries. We included publications between 2010 and May 2021 that reported primary data on concurrent HIV/STI testing. We conducted a random‐effects meta‐analysis and meta‐regression of the pooled proportion for concurrent HIV/STI testing. Results: We identified 96 eligible studies. Among those, 49 studies had relevant data for a meta‐analysis. The remaining studies provided data on the acceptability, feasibility, barriers, facilitators, economic evaluation and social harms of concurrent HIV/STI testing. The pooled proportion of people tested for HIV among those attending an STI service ( n = 18 studies) was 71.0% (95% confidence intervals: 61.0–80.1, I 2 = 99.9%), people tested for HIV among those who were tested for STIs ( n = 15) was 61.3% (53.9–68.4, I 2 = 99.9%), people tested for HIV among those who were diagnosed with an STI ( n = 13) was 35.3% (27.1–43.9, I 2 = 99.9%) and people tested for HIV among those presenting with STI symptoms ( n = 3) was 27.1% (20.5–34.3, I 2 = 92.0%). The meta‐regression analysis found that heterogeneity was driven mainly by identity as a sexual and gender minority, the latest year of study, country‐income level and region of the world. Discussion: This review found poor concurrent HIV/STI testing among those already diagnosed with an STI (35.3%) or who had symptoms with STIs (27.1%). Additionally, concurrent HIV/STI testing among those tested for STIs varied significantly according to the testing location, country income level and region of the world. A few potential reasons for these observations include differences in national STI‐related policies, lack of standard operation procedures, clinician‐level factors, poor awareness and adherence to HIV indicator condition‐guided HIV testing and stigma associated with HIV compared to other curable STIs. Conclusions: Not testing for HIV among people using STI services presents a significant missed opportunity, particularly among those diagnosed with an STI. Stronger integration of HIV and STI services is urgently needed to improve prevention, early diagnosis and linkage to care services.